Decreasing brown bear (Ursus arctos) habitat due to climate change in Central Asia and the Asian Highlands. Issue 23 (20th November 2018) - Su, Junhu; Aryal, Achyut; Hegab, Ibrahim M.; Shrestha, Uttam Babu; Coogan, Sean C. P.; Sathyakumar, Sambandam; Dalannast, Munkhnast; Dou, Zhigang; Suo, Yila; Dabu, Xilite; Fu, Hongyan; Wu, Liji; et al.
Abstract: Around the world, climate change has impacted many species. In this study, we used bioclimatic variables and biophysical layers of Central Asia and the Asian Highlands combined with presence data of brown bear ( Ursus arctos ) to understand their current distribution and predict their future distribution under the current rate of climate change. Our bioclimatic model showed that the current suitable habitat of brown bear encompasses 3, 430, 493 km 2 in the study area, the majority of which (>65%) located in China. Our analyses demonstrated that suitable habitat will be reduced by 11% (378, 861.30 km 2 ) across Central Asia and the Asian Highlands by 2, 050 due to climate change, predominantly (>90%) due to the changes in temperature and precipitation. The spatially averaged mean annual temperature of brown bear habitat is currently −1.2°C and predicted to increase to 1.6°C by 2, 050. Mean annual precipitation in brown bear habitats is predicted to increase by 13% (from 406 to 459 mm) by 2, 050. Such changes in two critical climatic variables may significantly affect the brown bear distribution, ethological repertoires, and physiological processes, which may increase their risk of extirpation in some areas. Approximately 32% (1, 124, 330 km 2 ) of the total suitable habitat falls within protected areas, which was predicted to reduce to 1, 103, 912 km 2 (1.8% loss) by 2, 050. Future loss of suitable habitats inside the protected areas may force brown bears to move outside the protected areas thereby increasing their risk of mortality. Therefore, more protected areas should be established in the suitable brown bear habitats in future to sustain populations in this region. Furthermore, development of corridors is needed to connect habitats between protected areas of different countries in Central Asia. Such practices will facilitate climate migration and connectivity among populations and movement between and within countries. Abstract : Climatic change may decrease brown bear's suitable habitat. Decrease suitability might consecutively increase possible human–bear conflicts. Our results help to manage brown bear populations and design future conservation policies. More protected areas and corridors should be established to connect habitats.